Clinical phenotype and genetic analysis of RPS19, RPL5, and RPL11 genes in Greek patients with Diamond Blackfan Anemia. Issue 12 (17th August 2014) - Delaporta, Polyxeni; Sofocleous, Christalena; Stiakaki, Eftichia; Polychronopoulou, Sophia; Economou, Marina; Kossiva, Lydia; Kostaridou, Stavroula; Kattamis, Antonis
<x xml:space="preserve">Abstract</x> Background Diamond Blackfan Anemia (DBA) is a rare congenital, bone marrow failure syndrome characterized by normochromic macrocytic anemia, reticulocytopenia and absence or insufficiency of erythroid precursors in normocellular bone marrow, frequently associated with somatic malformations. Here, we present our findings from the study of 17 patients recorded in the Greek DBA registry. Procedure Clinical evaluation of patients and data collection was performed followed by the molecular analysis of RPS19, RPL5, and RPL11 genes. Mutation screening included PCR amplification, ECMA analysis, and direct sequencing. Results Congenital anomalies were observed in 71% of the patients. Six patients (35.2%) were found to carry mutations on either the RPS19 gene (three patients, ) or the RPL5 gene (three patients). Mutations c.C390G (p.Y130X) and c.197_198insA (p.Y66X) detected in the RPL5 gene were novel. No mutations at the RPL11 gene were identified in Greek patients with DBA. Conclusions The clinical course of the patients was similar to previous reports. The occurrence of thyroid carcinoma in an adult patient with DBA is the first to be reported in DBA. Pediatr Blood Cancer 2014;61:2249–2255. © 2014 Wiley Periodicals, Inc.